Upaya Peningkatan Hasil Belajar Kognitif Siswa melalui Model Pembelajaran RCCDE - M Abdul Wafi; Siti Roudlotul Hikamah; Umi Nurjanah (FKIP Universitas Islam Jember, 2026)
This study was conducted with the aim of examining the improvement of student learning outcomes, especially in cognitive abilities, by applying the Reading Concept Connection Discussion Evaluation (RCCDE) learning model. This study was conducted through Classroom Action Research (PTK), using 2 cycles, with the following stages: 1) planning; 2) implementation of the action; 4) observation; 4) reflection. The subjects used were 21 students, namely 11 males and 10 females. Data were collected at the end of each cycle through a test of learning outcomes. The resulting analysis informed that there was a gradual increase in learning outcomes. In the pre-cycle, the level of student learning completeness was at 33% (average value of 60.9). In cycle I, completeness increased to 57% (average value of 74.5), while in cycle II there was another increase to 81% (average value of 83.8). The findings in this study inform that the RCCDE model is recommended to be one of the learning models that can be used in learning.